An In-Depth Study of Cost Components and Their Impact on Financial Performance at Jawahar Sahakari Soot Girni Limited - Sawalkar, Rutuja Kishorrao; Khaire, Megha (Journal of Neonatal Surgery, 2025)
The study explores the cost components within Jawahar Sahakari Soot Girni Limited and analyses their influence on the company’s overall financial performance. By examining key cost elements such as raw material expenses, labour costs, overheads, and capital expenditures, the research aims to uncover how these factors contribute to the firm's profitability and operational efficiency. Through a comprehensive assessment of cost structures and financial statements, the study identifies critical areas where cost management practices can be optimized for better financial health. Additionally, the research investigates the relationship between cost control mechanisms and the firm’s long-term sustainability. A detailed analysis of historical financial data is utilized to highlight trends in cost allocation and their corresponding effects on revenue generation. The findings offer actionable insights that can assist in formulating strategies to enhance cost-effectiveness and, in turn, improve the company’s financial standing. In doing so, the paper adds valuable knowledge to the field of financial performance analysis, specifically in the context of cooperative industries like Soot Girni mills. The study concludes with recommendations for better integration of cost management practices that align with financial goals and ensure competitive advantage in the market